The politics of educational reform in Alberta - Taylor, Alison, 1959- (Book collections on Project MUSE., 2001)
The Politics of Educational Reform in Alberta presents a case study of educational restructuring in Alberta during the 'Klein revolution' - the period of dramatic political and economic change introduced by Premier Ralph Klein's Conservative government of the 1990s. The government's 1994 business plan introduced funding cuts in education, the amalgamation of school boards, the centralization of funding, charter school legislation, expanded provincial testing, and mandatory school councils. The buzzwords for education reform were efficiency, accountability, and choice. Alison Taylor rigorously examines Klein's 'three-year plan' of school reform to unveil the ways in which the Alberta government allied itself with corporate interests. She also examines what happens to the voices of teachers, parents and labour groups who have a different idea of what school should be. The Politics of Educational Reform in Alberta is a timely and much-needed book. This multi-faceted view of corporate involvement in schooling will be invaluable to policy makers, educators, academics, journalists, and concerned parents.